THE COMPARISON OF THE EFFECT OF HONEY AND CHLORHEXIDINE IN PREVENTING VENTILATOR ASSOCIATED PNEUMONIA IN PATIENTS ON MECHANICAL VENTILATON - Syaukia Adini; Bedjo Santoso; Sarkum Sarkum; Sudirman Sudirman (Belitung Nursing Journal, 2018)
Background: Ventilator Associated Pneumonia (VAP) is one of the causes of infection in the hospital and the main cause of death due to nosocomial infection. The strategy to prevent VAP is by oral hygiene. Honey may be a good solution for oral hygiene. Objective: This study aims to compare the effect of the use of 20% honey solution and 0.2% chlorhexidine as oral hygiene on VAP prevention in patients on mechanical ventilation. Methods: This was a quasi-experimental study with posttest only control group design in an incentive care unit of a general hospital in Indonesia. Thirty respondents were selected using consecutive sampling, which 15 respondents assigned in a 20% honey group and 0.2% chlorhexidine group. Clinical Pulmonary Infection Score (CPIS) was used to measure Ventilator Associated Pneumonia. Data were analyzed using Independent t-test. Results: The mean of CPIS in the honey group was 3.33 and the chlorhexidine group was 3.53. Independent t-test showed p-value 0.618 (>0.05), which indicated that there was no significant difference of the effect of honey and chlorhexidine on VAP event. Conclusion: The 20% honey solution has the same effect with 0.2% chlorhexidine in preventing VAP events in patients on mechanical ventilation.